2011
DOI: 10.1002/aic.12664
|View full text |Cite
|
Sign up to set email alerts
|

A novel dynamic membrane reactor concept with radial‐flow pattern for reacting material and axial‐flow pattern for sweeping gas in catalytic naphtha reformers

Abstract: Naphtha reforming units are of high interest for hydrogen production in refineries. In this regard, the application of membrane concept in radial‐flow tubular naphtha reactors for hydrogen production is proposed. Because of the importance of the pressure drop problem in catalytic naphtha reforming units, the radial‐flow reactors are proposed. A radial‐flow tubular membrane reactor (RF‐TMR) with the radial‐flow pattern of the naphtha feed and the axial‐flow pattern of the sweeping gas is proposed as an alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Hydrogen produced in catalytic reforming has become increasingly valuable, because it is used in hydroprocessing units for the removal of sulfur and nitrogen, as well as the hydrocracking . Figures a–c shows the molar flow rates of various products obtained from the naphtha section of the coupled reactors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen produced in catalytic reforming has become increasingly valuable, because it is used in hydroprocessing units for the removal of sulfur and nitrogen, as well as the hydrocracking . Figures a–c shows the molar flow rates of various products obtained from the naphtha section of the coupled reactors.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen produced in catalytic reforming has become increasingly valuable, because it is used in hydroprocessing units for the removal of sulfur and nitrogen, as well as the hydrocracking. 59 Overall Heat-Transfer Coefficient According to this figure, the hydrogen and aromatic production rate in NR-CLC are higher than those in CNR; hence, Figure 5 reveals the preference of NR-CLC configuration to the CNR configuration since a higher hydrogen and aromatic production rate is achieved at the end of the third reactor. As is seen, the hydrogen and aromatic production rate in outlet of the second reactor in the coupled reactors is higher than that in outlet of the third reactor in CNR.…”
Section: Boundary and Initial Conditionsmentioning
confidence: 99%
“…Hence, the pressure drop within a radial flow catalyst bed is much less compared to the axial flow catalyst bed. Detailed description of the pressure drop advantage for a radial flow reactor compared with an axial flow reactor can be found in the literature. In 2011, Iranshahi et al have proposed a radial flow tubular membrane reactor instead of conventional axial flow tubular reactors for naphtha reforming units . They have reported that the product yield has been increased and smaller catalyst particles with better efficiency can be utilized in a radial flow tubular membrane reactor due to a small pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…Several configurations such as fixed bed with hydrogen permselective membrane reactor, radial-flow assisted membrane naphtha reactor, and axial flow spherical packed bed membrane reactor have been suggested to boost the performance of the membrane reactor.…”
Section: Introductionmentioning
confidence: 99%